A Practical Recovery Strategy for Delayed Construction Project: Insights from a Geothermal Cooling Tower Case - Hilarius Yuda Kusuma Anuraga; Gatot Yudoko (Publikasi Indonesia, 2025)
Project delays in construction often lead to significant financial consequences, particularly in terms of penalties specified in the project contract. This study addresses the cost-efficiency consideration behind the decision to implement project crashing through overtime, as opposed to accepting the penalty due to project delay. The research uses a case study of a geothermal power plant renovation project in Indonesia, which faced a ten-week delay caused by external factors. The study compares the penalty potential with the total cost of project crashing calculated. The results reveal that accelerating activities on the critical path only costs 17.02% of the potential penalty if no corrective actions are taken. This analysis emphasizes the importance of financial trade-offs in project decision-making and highlights that project crashing, when planned and executed properly, is a rational and cost-efficient strategy to recover from delays, provided it does not compromise project quality and scope. The study contributes to understanding the financial implications of project acceleration and offers insights for managers considering delay recovery strategies.